(untitled) (Fiep Bulletin - online, 2017)
Perception of physical education students on sports mega events: 2014 FIFA World Cup and 2016 Olympic GamesThe sport mega-events have been researched by many scholars (Carvalho et al, 2008; CAVALLI et al, 2008). Theobjective of this study is to understand the perception of physical education students about the sport mega-events in Rio deJaneiro, Brazil. This research used the student perceptions concerning to the mega-event as the methodological basis asrecommended by Sousa e Silva (2008), Mataruna (2008) and Mihalik (2002). It was applied a questionnaire to the sample of 249people volunteers, 167 men and 82 women. Most of the people interviewed realized that the events will have a little influence onworking conditions (57%); the recognizement of the PE teachers (55%); personal life (49%); and living conditions of thepopulation (56%); (61%) reported the perception of opportunities and new business in the area of physical education.